2002
DOI: 10.1300/j070v11n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Intimacy, Loneliness and Locus of Control in Child Sex Offenders: A Comparison Between Familial and Non-Familial Child Sexual Offenders

Abstract: There has been relatively little previous research examining differences between subgroups of child sex offenders. In this study, we compared a group of familial and non-familial child sex offenders attending a community based treatment program on a number of relationship dimensions thought to be important in explaining offending. No statistically significant differences were found between these groups on measures of general empathy, intimacy and loneliness, although non-familial offenders were found to have h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…Most researchers now distinguish between offenders who have sexually assaulted adult women (rapists) and offenders who have sexually abused children (child molesters) (Knight & Prentky, 1990;Simon, 1997aSimon, , 1997b. Further distinctions are also typically made between familial (incest) and non-familial child molesters (Parton & Day, 2002). Only two typological systems for rapists and child molesters have had extensive empirical validation (Knight, 1992;Knight & Guay, 2006).…”
Section: Sexual Offendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers now distinguish between offenders who have sexually assaulted adult women (rapists) and offenders who have sexually abused children (child molesters) (Knight & Prentky, 1990;Simon, 1997aSimon, , 1997b. Further distinctions are also typically made between familial (incest) and non-familial child molesters (Parton & Day, 2002). Only two typological systems for rapists and child molesters have had extensive empirical validation (Knight, 1992;Knight & Guay, 2006).…”
Section: Sexual Offendingmentioning
confidence: 99%
“…In fact, if a specialist persistent offender exists, the stereotypical extra-familial child molester is likely the most convincing example. It has been concluded that when compared to rapists, a child molester's pattern of sexual offending continues longer, with more frequency, and with a higher number of victims (Parton & Day, 2002). Research has indicated that men who commit child abuse exclusively within the home most closely resemble non-offenders on a variety of variables (Marshall, 1988).…”
Section: Sexual Offendingmentioning
confidence: 99%
“…Higher scores are indicative of higher levels of loneliness and half the items are negatively worded. The UCLA is one of the most frequently used measures of loneliness (Jones & Hebb, 2003) and has been previously used with offenders (Ireland & Power, 2004;Parton & Day, 2002;Segrin, 2003). Previous research using this measure suggests that it is highly reliable in its internal consistency (coefficient alpha ranging from .89 to .94) and test-retest reliability over a 1-year period (r ¼ .73) (Russell, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…However, the relationship between external LOC and offending is less clear when offence type is considered. Much research effort has focused on LOC amongst offenders who have committed sexual offences (Adolfsson et al, 2005;Fisher et al, 1998;Parton and Day, 2002), whilst less emphasis has been placed upon other areas of offending such as violence, drugs or property offences. Therefore, evidence concerning the significance of LOC is primarily found in sex offender research.…”
Section: Loc In Offender Populationsmentioning
confidence: 99%